TbMYC4A Is a Candidate Gene Controlling the Blue Aleurone Trait in a Wheat-Triticum boeoticum Substitution Line - Liu, Xin; Zhang, Minghu; Jiang, Xiaomei; Li, Hui; Jia, Zhenjiao; Hao, Ming; Jiang, Bo; Huang, Lin; Ning, Shunzong; Yuan, Zhongwei; Chen, Xuejiao; Chen, Xue; et al. (Frontiers in Plant Science, 2021)
Triticum boeoticum Boiss (AbAb, 2n = 2x = 14) is one of the sources of the blue grain trait controlled by blue aleurone layer 2 (Ba2). However, the underlying genes have not been cloned. In this study, a transcriptomic comparison between a blue-grained wheat-T. boeoticum substitution line and its wheat parent identified 41 unigenes related to anthocyanin biosynthesis and 29 unigenes related to transport. The bHLH transcription factor gene TbMYC4A showed a higher expression level in the blue-grained substitution line. TbMYC4A contained the three characteristic bHLH transcription factor domains (bHLH-MYC_N, HLH and ACT-like) and clustered with genes identified from other wheat lines with the blue grain trait derived from other Triticeae species. TbMYC4A overexpression confirmed that it was a functional bHLH transcription factor. The analysis of a TbMYC4A-specific marker showed that the gene was also present in T. boeoticum and T. monococcum with blue aleurone but absent in other Triticeae materials with white aleurone. These results indicate that TbMYC4A is a candidate gene of Ba2 controlling the blue aleurone trait. The isolation of TbMYC4A is helpful for further clarifying the genetic mechanism of the blue aleurone trait and is of great significance for breeding blue-grained wheat varieties.